2009
DOI: 10.1123/apaq.26.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Self-Determination and Leisure Experiences of Women Living in Two Group Homes

Abstract: This phenomenological case study examined the leisure experiences of five women with intellectual disabilities (ages 44–60) in two group homes. Using participant observation, artifacts, and semistructured interviews, the nature of the women’s leisure experiences were understood within the conceptual framework of self-determination. Five staff members were also interviewed to further contextualize the women’s leisure experiences. Thematic analysis revealed three main themes: leisure at home, leisure in the comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The influence exerted in the processes of decision support was very evident by the way supporters framed particular decisions, presented options and managed risk. In many instances, their actions reflected examples found in the literature of support based on paternalism, best interest, or values and self-interest of the supporter (Dunn et al, 2010;Ferguson et al, 2011;Rossow-Kimball & Goodwin, 2009). Workers appeared more concerned than family members about influencing decisions and their aspirations to be neutral and reflective were similar to the way social workers talk about suspending their own judgments and adopting a neutral and non-judgmental stance to supporting decision making (Ellem, O'Connor, Wilson, & Williams, 2013).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The influence exerted in the processes of decision support was very evident by the way supporters framed particular decisions, presented options and managed risk. In many instances, their actions reflected examples found in the literature of support based on paternalism, best interest, or values and self-interest of the supporter (Dunn et al, 2010;Ferguson et al, 2011;Rossow-Kimball & Goodwin, 2009). Workers appeared more concerned than family members about influencing decisions and their aspirations to be neutral and reflective were similar to the way social workers talk about suspending their own judgments and adopting a neutral and non-judgmental stance to supporting decision making (Ellem, O'Connor, Wilson, & Williams, 2013).…”
Section: Discussionmentioning
confidence: 76%
“…For example, positive attitudes of others towards risk, and creation of opportunities for choice enable increased involvement in decision making (Kjellberg, 2002;Mill, Mayes, & McConnell, 2010;Timmons, Hall, Bose, Wolfe, & Winsor, 2011). The relationship between the supporter and the person being supported has been highlighted as an important factor in the process of providing decision support (Burgen, 2010;Kjellberg, 2002), as has tailoring of support and communication to the needs and skills of the individual in the context of formal meetings as well as more individualised interactions (Antaki, Finlay, Walton, & Pate, 2008;Conder, Mirfin-Veitch, Sanders, & Munford, 2011;Espiner & Hartnett, 2012;Rossow-Kimball & Goodwin, 2009). Specific strategies such as staff practice based on active support have also been found to play a role in shaping participation in choice and decision making (Beadle-Brown, Hutchinson, & Whelton, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the psychosocial issues, a variety of studies examined e.g. the psychosocial determinants of sports (Dunn & Dunn, 2006;Perreault & Vallerand, 2007;Harada & Siperstein, 2009;Shapiro & Martin, 2010), leisure experience (Rossow-Kimball & Goodwin, 2009), quality of life (Giacobbi et al, 2008), parental expectations (Goodwin et al, 2006;An & Goodwin, 2007;Columna et al, 2008), etc. The measurement/ assessment /classification area included topics relative to validity (Van Waelvelde et al, 2007;Loh et al, 2009) and reliability (Driver, 2007;Motl et al, 2007) testing, sport classification issues for individuals with disabilities (Beets et al, 2007;Molik et al, 2008), etc.…”
Section: Discussionmentioning
confidence: 99%
“…Across the body of research a number of supporter characteristics and skills were identified as enabling people with cognitive disability to participate in decision making. Examples of enabling characteristics included supporters having a positive attitude towards people with cognitive disability exercising choice, control, and creating decision making opportunities [30,33,[38][39][40][41][42][43]; being self-aware; able to suspend one's own judgments and able to adopt a neutral and non-judgmental stance in providing support for decision making [37]; having a positive relationship with the individual based on trust and understanding [31,[33][34][35]; knowing about a person's cognitive impairment and being able to adjust support and communication to the strengths and weaknesses of the individual [33,[44][45][46].…”
Section: Reviewing the Literaturementioning
confidence: 99%